Black women and popular culture : the conversation continues - Goldman, Adria Y. (Lexington Books, 2014)
Black Women and Popular Culture: The Conversation Continues provides cutting-edge research in its analysis of the representation of Black women in popular culture and the potential implications of those images and messages. This compilation inspires critical thought and adds to the discussion on the various roles of Black women in popular culture.